2015
DOI: 10.1186/s12933-015-0184-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of adiponectin and free fatty acids on the association between abdominal visceral fat and insulin resistance

Abstract: BackgroundExperimental studies have shown that high free fatty acid (FFA) and low adiponectin (ADIPO) levels are involved in the mechanisms by which adiposity promotes insulin resistance (IR). However, no previous clinical studies have simultaneously analysed the relative contribution of FFA and ADIPO levels on the relation of abdominal visceral fat (AVF) with insulin resistance.ObjectiveTo analyse the contribution of low ADIPO (adiponectin < =p25th: 8.67 μg/mL in women and 5.30 μg/mL in men), and high FFAs (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 38 publications
(42 reference statements)
2
42
0
2
Order By: Relevance
“…Previous reports suggested that visceral adiposity induces insulin resistance by a mechanism that involves high FFA and/or low adiponectin plasma levels (89,90). Data from our research group confirmed that low adiponectin was an independent predictor of insulin resistance, even after adjusting for confounders such as FFA and VAT (91). Therefore, low adiponectin may be a useful biomarker of dysfunctional adiposity and may improve the identification of subjects at high risk for T2DM and CAD.…”
Section: Adipose Tissue In the Pathophysiology Of Metssupporting
confidence: 78%
“…Previous reports suggested that visceral adiposity induces insulin resistance by a mechanism that involves high FFA and/or low adiponectin plasma levels (89,90). Data from our research group confirmed that low adiponectin was an independent predictor of insulin resistance, even after adjusting for confounders such as FFA and VAT (91). Therefore, low adiponectin may be a useful biomarker of dysfunctional adiposity and may improve the identification of subjects at high risk for T2DM and CAD.…”
Section: Adipose Tissue In the Pathophysiology Of Metssupporting
confidence: 78%
“…Its production by adipocytes is inhibited by pro-inflammatory factors (e.g., TNF-α, IL-6), hypoxia, and oxidative stress [35]. Low adiponectin concentrations are associated with visceral fatness, which is a risk factor for insulin resistance [36,38]. There are several possible reasons why we did not observe dose effects in intention-to-treat analyses.…”
Section: Friedenreich Et Almentioning
confidence: 89%
“…2016;6(2): [35][36][37][38][39][40][41][42][43][44][45] high, n = 9 moderate). Moreover, we did not measure peripheral insulin resistance in muscle or fat, which may be relevant to breast cancer etiology.…”
Section: Statistical Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperinsulinemia is often seen in obese individuals and postprandial insulin resistance is a critical determinant of obesity in children [17]. Insulin that promotes energy storing in adipose tissue is considered as the prime suspect of obesity and the target of therapy [18,19]. In the treatment of hypothalamic obesity, SST and its analogues limit the release of insulin and inhibit adipogenesis [20].…”
Section: Introductionmentioning
confidence: 99%